2002
DOI: 10.4141/p01-061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant age and cottony snow mold on winter survival of forage grasses

Abstract: . Effect of plant age and cottony snow mold on winter survival of forage grasses. Can. J. Plant Sci. 82: 701-708. The low temperature basidiomycete (LTB, syn. Copribus psychromorbidus Traquair), the causal agent of cottony snow mold, is a major constraint to forage grass survival and productivity in the parkland region of the Canadian prairies under prolonged snow cover (e.g., 160 d). Studies were conducted to establish the level of the snow mold resistance in seven grass species commonly grown in western Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Kohn. ], but in the parkland region of the Canadian prairies, its tolerance of snow molds exceeds that of other common forages (Hwang et al 2002) (Myhr et al 1966).…”
Section: Response To Herbivory Disease and Higher Plant Parasitesmentioning
confidence: 99%
“…Kohn. ], but in the parkland region of the Canadian prairies, its tolerance of snow molds exceeds that of other common forages (Hwang et al 2002) (Myhr et al 1966).…”
Section: Response To Herbivory Disease and Higher Plant Parasitesmentioning
confidence: 99%
“…During this research no correlations between winter hardiness and resistance to snow mould were observed. It is well established that the role of snow mould resistance in winter hardiness and the relationship between snow mould and frost resistance may differ both among plant and fungi species and that they are strongly affected by climatic conditions (Larsen, 1994;Gaudet, 1994;Hwang et al, 2002). Many studies in winter cereals have similarly found no correlation between frost tolerance and snow mould resistance even under laboratory conditions (Gaudet & Kozub, 1991;Iriki et al, 2001).…”
Section: Discussionmentioning
confidence: 91%
“…Rate of growth after the snow has melted infl uences the yield of the fi rst harvest for hay-making at the heading stage. Plant size before winter aff ects winter hardiness (Hwang et al, 2002), freezing tolerance (Hofgaard et al, 2003), and resistance to snow mold (Amano, 1987;Hwang et al, 2002;Hofgaard et al, 2003) in grasses and cereals. Temperate grass germplasm originating from northern regions, such as in Europe, have shown good winter hardiness in Hokkaido (Nakayama and Abe, 1996;Nakayama et al, 1997).…”
Section: Researchmentioning
confidence: 99%